A Physiologically Based Pharmacokinetic Model of Mitoxantrone in Mice and Scale-up to Humans: a Semi-Mechanistic Model Incorporating DNA and Protein Binding - An, Guohua (Springer US, 2012)
We conducted a pharmacokinetic (PK) study of mitoxantrone (Novantrone®), a clinically well-established anticancer agent, in mice and developed a mechanism-based PBPK (physiologically based pharmacokinetic) model to describe its disposition. Mitoxantrone concentrations in plasma and six organs (lung, heart, liver, kidney, spleen, and brain) were determined after a 5 mg/kg i.v. dose. We evaluated three different PBPK models in order to characterize our experimental data: model 1 containing Kp values, model 2 incorporating a deep binding compartment, and model 3 incorporating binding of mitoxantrone to DNA and protein. Among the three models, only model 3 with DNA and protein binding captured all the experimental data well. The estimated binding affinity for DNA (K(DNA)) and protein (K(macro)) were 0.0013 and 1.44 μM, respectively. Predicted plasma and tissue AUC values differed from observed values by <19 %, except for heart (60 %). Model 3 was further used to simulate plasma mitoxantrone concentrations in humans for a 12-mg/m(2) dose, using human physiological parameters. The simulated results generally agreed with the observed time course of mitoxantrone plasma concentrations in patients after a standard dose of 12 mg/m(2). In summary, we reported for the first time a mechanism-based PBPK model of mitoxantrone incorporating macromolecule binding which may have clinical applicability in optimizing clinical therapy. Since mitoxantrone is a substrate of the efflux transporters ABCG2 and ABCB1, the incorporation of efflux transporters may also be necessary to characterize the data obtained in low-dose studies.